Optical coherence tomography evaluation of patients with macula‐off retinal detachment after different postoperative posturing: a randomized pilot study. Issue 5 (26th April 2017) - Peiretti, Enrico; Nasini, Francesco; Buschini, Elisa; Caminiti, Giulia; Lesnik Oberstein, Sarit Y.; Willig, Alissa; Bijl, Heico M.; Mura, Marco
Abstract: Purpose: To assess the presence of outer and inner retinal folds (RFs) and drop‐out of the ellipsoid zone (EZ) occurring after surgical repair of macula‐off rhegmatogenous retinal detachment (RRD) with different postoperative posture and preoperative use of adjuvant perfluorocarbon liquid (PFCO). Methods: In this prospective study, 56 eyes of 56 consecutive patients affected by RRD were subjected to 23‐ or 25‐gauge pars plana vitrectomy (PPV). The patients were randomized in four groups (14 prone 5 hr without PFCO, 14 supine 5 hr without PFCO, 14 prone 5 hr with PFCO and 14 supine 5 hr with PFCO) and followed up with spectral domain optical coherence tomography (SD‐OCT). Results: Spectral domain optical coherence tomography (SD‐OCT) was recorded before surgery, at days 30 and 90 to detect the presence of outer RFs, inner RFs and drop‐out of EZ and to follow their variation over time. No statistical significance was found in our groups for outer RFs, inner RFs, drop‐out of EZ formation and evolution. The postoperative best‐corrected visual acuity (BCVA) improved in all groups (mean preoperative BCVA 1.47 logMar ± 0.19, mean postoperative BCVA 0.27 logMar ± 0.11, p < 0.01), without statistical variations between the four groups in BCVA after surgery. Conclusion: The use of adjuvant and variation in postoperative position did not change the risk of presenting outer RFs, inner RFs and drop‐out of EZ after RRD.